2011
DOI: 10.1161/atvbaha.111.227629
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interleukin 17 in Inflammation, Atherosclerosis, and Vascular Function in Apolipoprotein E–Deficient Mice

Abstract: Objective Interleukin 17A (IL17A) is involved in many inflammatory processes but its role in atherosclerosis remains controversial. We examined the role of IL17A in mouse and human atherosclerosis. Methods and Results Atherosclerosis was induced in ApoE−/− and IL17A/ApoE−/− mice using high fat feeding, angiotensin II infusion, or partial carotid ligation. In ApoE−/− mice, 3 months of high fat diet induced interferon gamma production by splenic lymphocytes, and this was abrogated in IL17A/ApoE−/− mice. IL17A/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
159
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(171 citation statements)
references
References 38 publications
8
159
1
3
Order By: Relevance
“…Luminal occlusion was not directly examined (21). Consistent with our findings, Madhur et al (46) showed recently that IL-17 does not affect intimal thickening but supports outward remodeling in a mouse model of atherosclerosis. Finally, an alternative explanation for the negative correlation between IL-17-positive cells and luminal occlusion that we observe could be that IL-17 responses predominate early in allogeneic responses.…”
Section: Discussionsupporting
confidence: 82%
“…Luminal occlusion was not directly examined (21). Consistent with our findings, Madhur et al (46) showed recently that IL-17 does not affect intimal thickening but supports outward remodeling in a mouse model of atherosclerosis. Finally, an alternative explanation for the negative correlation between IL-17-positive cells and luminal occlusion that we observe could be that IL-17 responses predominate early in allogeneic responses.…”
Section: Discussionsupporting
confidence: 82%
“…Atherosclerosis and its consequences (i.e., myocardial infarction and stroke) remain the major cause of morbidity and mortality in Western countries. Several studies have investigated the role of IL-17A in the development of atherosclerosis with partially controversial results (7)(8)(9)(10)(11)(24)(25)(26), which are at least partially based on the study design, neutralizing Ab versus bone marrow transfer experiments, on the type of diet, and on the location of the analysis of the atherosclerotic lesion. By contrast, the current study evaluated the role of IL-17A on advanced atherosclerotic lesions and its potential impact as a therapeutic target.…”
Section: Synergistic Effects Of Il-17a In Addition To Lps In the Plaqmentioning
confidence: 99%
“…8,9 According to previous studies, Th1 cells induce plaque rupture and the onset of acute coronary syndrome (ACS), and Th17 cells contribute to vascular and systemic inflammation and may modulate plaque stability, whereas Treg cells play the opposite role. 10,11 However, the underlying molecular mechanisms of the imbalance of Th cells in atherosclerosis have not been thoroughly clarified. Recently, miRNAs (such as miR-155 and miR-146a) were determined to be key molecules in modulating the differentiation of Th cells.…”
Section: Introductionmentioning
confidence: 99%